Diagnostic Accuracy of Mammography Versus Ultrasound in Prediction of Malignancy with Palpable Breast Lesion - Mazhar Shafiq; Akhter; Lubna Shamshad; Nisar Ahmed; Sadaf Saleem; Rahat Shahid; Shumaila; Muhammad Ali Mazhar (ziauddin University, 2024)
Background: Breast malignancy is globally the most prevalent type of cancer. Early and appropriate screening is important for proper treatment. Ultrasonography (USG) is extensively useful as an adjunct to mammography in clinical practice. This study aimed to compare the diagnostic accurateness of mammography versus ultrasound imaging in predicting breast malignancies in women with palpable lesions using histopathology as the gold standard. Methods: The bilateral mammography was performed on 100 patients of age 35-80 years in the Radiology department, PNS Shifa hospital, Karachi. Bilateral whole-breast USG was also performed and findings were recorded. Then histopathology was done by taking samples (localized solid swelling fixed to breast tissue and skin feeling different from normal breast parenchyma, present more than 1 month) through TruCut 18 G needle and compared with mammography and ultrasound. The data was analyzed by SPSS and a screening test was applied to check the sensitivity and specificity. Results: The mean age of the patients (n=100) was 58.91±13.46 years. The USG diagnosed malignant breast lesions in 46% and benign breast lesions in 54% of patients. Whereas, by mammography, malignancy was diagnosed in 47% and benign in 53% of patients. The USG tool showed 69.64% sensitivity, 84.09% specificity, 84.78% negative predictive value (NPV), 68.52% positive predictive value (PPV) and 76% diagnostic accuracy, respectively. However, mammography had 60.71% sensitivity, 70.45% specificity, 72.34% NPV, 58.49% PPV and 65% accuracy, while considering histopathology as the gold standard. Conclusion: The ultrasonography (USG) was found more sensitive than mammography in the prediction of breast malignancy presenting with palpable breast lesions. Keywords: Mammography; Ultrasonography; Accuracy; Histopathology; Breast Cancer.